2017
DOI: 10.1186/s12967-017-1222-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression profile of HCMV encoded miRNAs in plasma from oral lichen planus patients

Abstract: BackgroundOral lichen planus (OLP) is a T cell-mediated autoimmune disease. The aetiology and molecular mechanisms of OLP remain unclear. Human cytomegalovirus (HCMV) infection is a causal factor in the development of various diseases, but the clinical relevance of HCMV in OLP has not been thoroughly investigated.MethodsIn the present study, we firstly examined twenty-three HCMV-encoded microRNA (miRNA) expression profiles in plasma from training set that including 21 OLP patients and 18 healthy controls using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…More interestingly, recent studies revealed that viruses can hijack the exosome pathway, and virus-encoded miRNAs can be actively secreted via exosomes from virus-infected cells and delivered to and act in virus-negative recipient cells [34]. Furthermore, our latest study implied that specifically altered plasma HCMV miRNA is primarily encapsulated in exosomes [35]. Thus, taken together our findings combined with those previous reports, the exogenous HCMV-encoded miRNAs can be packaged into exosomes and delivered to recipient cells, moreover, the involvement of exosome-encapsulated HCMV-encoded miRNAs in host recipient cellular gene repression may also provide further insights into novel and somewhat surprising potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…More interestingly, recent studies revealed that viruses can hijack the exosome pathway, and virus-encoded miRNAs can be actively secreted via exosomes from virus-infected cells and delivered to and act in virus-negative recipient cells [34]. Furthermore, our latest study implied that specifically altered plasma HCMV miRNA is primarily encapsulated in exosomes [35]. Thus, taken together our findings combined with those previous reports, the exogenous HCMV-encoded miRNAs can be packaged into exosomes and delivered to recipient cells, moreover, the involvement of exosome-encapsulated HCMV-encoded miRNAs in host recipient cellular gene repression may also provide further insights into novel and somewhat surprising potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 72%
“…Oral lichen planus Upregulation [35] this disease remains elusive. By characterizing the plasma miRNAs pattern of patients with essential hypertension, Li and colleagues identified that the plasma concentrations of miR-UL112 were markedly higher in hypertensive patients than that in the control subjects.…”
Section: Serummentioning
confidence: 99%
“…Protein was extracted from tissues and cells by RIPA lysis buffer, and protein levels were analyzed via Western blotting and performed as described previously (26). The antibodies used for Western blotting were as follows: anti-SPOP antibody (ProteinTech; 16750-1-AP, 1:500), anti-E2F1 antibody (Cell Signaling Technology; #3742, 1:1,000), anti-PTEN antibody (Cell Signaling Technology; #9559, 1:1,000), anti-DUSP7 antibody (ABGENT; AP8450a, 1:500), anti-SP1 antibody (Abcam; ab227383,1:1,000), anti-c-Myc antibody (Cell Signaling Technology; #13987, 1:1,000), and anti-GAPDH antibody (Santa Cruz Biotechnology; sc-25778, 1:2,000).…”
Section: Western Blotting and Antibodiesmentioning
confidence: 99%
“…Comparatively, detection of hcmv-miR-UL22A-5p in transplant recipients with HCMV infections had the highest sensitivity for the prediction of subsequent virologic recurrence [16]. Our research group also demonstrated different expression pro le of HCMVencoded miRNAs in plasma sample from patients suffered with OLP, and 5 of the miRNAs including hcmv-miR-UL112-3p, hcmv-miR-UL22a-5p, hcmv-miR-UL148D, hcmv-miR-UL36-5p and hcmv-miR-UL59 were signi cantly upregulated in OLP samples compared with normal samples [17]. All these results indicate that these HCMV-encoded-miRNAs may share similar physiological and pathological roles in HCMV infection related diseases mentioned above, as well as in this study, even though much further study is needed to con rm this.…”
Section: Discussionmentioning
confidence: 54%
“…Total RNA was extracted from 100 µL of serum using a 1-step phenol/chloroform puri cation method and precipitated using isopropyl alcohol as previously described [17]. In brief, 100 µL of serum was mixed with 300 µL deionized water, 200 µL acid phenol, and 200 µL chloroform.…”
Section: Serum Rna Isolation and Rt-qpcr Assaymentioning
confidence: 99%